Use of the wearable cardioverter‐defibrillator among patients with myocarditis and reduced ejection fraction or ventricular tachyarrhythmia: data from a multicenter registry - El-Battrawy, Ibrahim; Koepsel, Katharina; Tenbrink, David; Kovacs, Boldizsar; Dreher, Tobias C.; Blockhaus, Christian; Gotzmann, Michael; Klein, Norbert; Kuntz, Thomas; Shin, Dong‐In; Lapp, Hendrik; Rosenkaimer, Stephanie; et al. (Journal of the American Heart Association, 2023)
Background - Data on the use of the wearable cardioverter‐defibrillator (WCD) among patients with myocarditis remain sparse. Consequently, evidence for guideline recommendations in this patient population is lacking. - Methods and Results - In total, 1596 consecutive patients were included in a multicenter registry from 8 European centers, with 124 patients (8%) having received the WCD due to myocarditis and reduced left ventricular ejection fraction or prior ventricular tachyarrhythmia. The mean age was 51.6±16.3 years, with 74% being male. Patients were discharged after index hospitalization on heart failure medication: Angiotensin‐converting enzyme inhibitors (62.5%), angiotensin‐receptor‐neprilysin inhibitor (22.9%), aldosterone‐antagonists (51%), or beta blockers (91.4%). The initial median left ventricular ejection fraction was 30% (22%-45%) and increased to 48% (39%-55%) over long‐term follow‐up (P<0.001). The median BNP (brain natriuretic peptide) level at baseline was 1702 pg/mL (565-3748) and decreased to 188 pg/mL (26-348) over long‐term follow‐up (P=0.022). The mean wear time was 79.7±52.1 days and 21.0±4.9 hours per day. Arrhythmic event rates documented by the WCD were 9.7% for nonsustained ventricular tachycardia, 6.5% for sustained ventricular tachycardia, and 0% for ventricular fibrillation. Subsequently, 2.4% of patients experienced an appropriate WCD shock. The rate of inappropriate WCD shocks was 0.8%. All 3 patients with appropriate WCD shock had experienced ventricular tachycardia/ventricular fibrillation before WCD prescription, with only 1 patient showing a left ventricular ejection fraction <35%. - Conclusions - Patients with myocarditis and risk for occurrence of ventricular tachyarrhythmia may benefit from WCD use. Prior ventricular arrhythmia might appear as a better risk predictor than a reduced left ventricular ejection fraction <35% in this population.
Online veröffentlicht: 8. September 2023
Gesehen am 08.08.2024